Supply Chains, Human Rights, Transnational Corporations and textile industry: from IFAs to a Legally Binding International Instrument. - Guamán, Adoración; Luque González, Arturo (Cuadernos de Relaciones Laborales, 2019)
The text is based on the need to develop internationally binding standards on transnational corporations and human rights in order to bring the impunity they enjoy to an end when, directly or along the different links of their supply chain, they provoke violations of these rights, as well as ensuring the reparation of the victims and possible consequences.There are different initiatives at international level, both within the United Nations (Guiding Principles) and within the scope of the corporations themselves and their relations with trade unions (International Framework Agreements), aimed at encouraging transnational companies to behave respectfully, aligned with the rights mentioned. However, and this is the fundamental thesis of the article, these initiatives continue to be insufficient, either because of their lack of obligation or because of their partial nature, dependent on the voluntariness of these transnational economic actors. In addition, the relationship between both sets of regulations, Guiding Principles and Framework Agreements, presents problems that a future Legally Binding Instrument on Transnational Corporations and Human Rights should solve. The fundamental objective of this article addresses the study of this question.